MENYEMBUNYIKAN ILMU PERSPEKTIF HADIS - Lenni Hidayati; Ilham Mustafa (Adisam Publisher, 2025)
Hiding knowledge is an act that is not good, because knowledge is something that is needed by humans in any case. Knowledge is also a guide or light that can illuminate a person, with knowledge a person can distinguish between good and bad. The more knowledge that is spread, the more knowledge will increase and develop. Therefore, if someone already knows a science, they must practice and teach it to others, because basically knowledge in Islam is to be practiced and taught, not just collected. Even people who do not want to convey or teach their knowledge to others will receive threats and torment as explained in the hadith. But what if the knowledge is related to skills (abilities). For example, a person's ability in the field of business or business. Is the person who has such knowledge obliged to convey his knowledge, and if he hides his knowledge is he among those who will be threatened according to the information in the hadith. Thus, the question arises, namely how to understand the Hadith about hiding knowledge. The purpose of this study is to find out the understanding of the Hadith about hiding knowledge. Then it is expected to bring benefits to add insight and understanding so that it can be used in everyday life.This research is classified as qualitative research of a library nature (Library Research), using the maudhu'i method which is useful for understanding the hadith, understanding the meaning of the hadith and capturing the meaning contained in the hadith by studying other related traditions on the same theme and paying attention to the correlation of each so as to produce a complete understanding. The result of this study is the hadith about hiding knowledge. Based on the understanding of the Hadith, it can be seen that not all knowledge is forbidden to be hidden. However, the knowledge that is forbidden to be hidden is the knowledge that a person needs in religious affairs, because this type of knowledge if hidden will have a bad impact on the life of the world and also the life of the hereafter. And the person who hides it will get torture and threats. As for knowledge related to the ability (skill) in the field of business or business is the science of the world and is not required to convey this knowledge. Likewise, knowledge or knowledge that can cause harm should not be conveyed.